2020
DOI: 10.1111/nmo.13916
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation ameliorates colonic barrier functions in a rodent model of colitis

Abstract: Background The mucosal barrier damage is recognized as one of the key factors in the pathogenesis of colitis. While sacral nerve stimulation (SNS) was reported to have therapeutic potential for colitis, its mechanisms of actions on colonic permeability remained largely unknown. Methods In this study, colitis was induced by intrarectal administration of TNBS in rats. Five days later, they were treated with SNS or sham‐SNS for 10 days. The effects of SNS on colonic permeability were assessed by measuring the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
4
18
0
Order By: Relevance
“…Jiang et al (2019b) demonstrated that SNS with appropriate parameters could improve VH via the autonomic pathway. While we have also shown that SNS could ameliorate the colonic permeability in animal mode of IBD (Tu et al, 2020b), its mechanisms of action involved in the ameliorating effect of SNS on VH needs further investigation. Thus, in this study, we induced VH by administrating acetic acid (AA) in a neonatal stage, which is a widely accepted IBS animal model.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Jiang et al (2019b) demonstrated that SNS with appropriate parameters could improve VH via the autonomic pathway. While we have also shown that SNS could ameliorate the colonic permeability in animal mode of IBD (Tu et al, 2020b), its mechanisms of action involved in the ameliorating effect of SNS on VH needs further investigation. Thus, in this study, we induced VH by administrating acetic acid (AA) in a neonatal stage, which is a widely accepted IBS animal model.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, in this study we used unilateral SNS on right sacral nerve of S3 to investigate the possible analgesic effects of SNS. Briefly, as we reported previously (Jiang et al, 2019b;Tu et al, 2020b), a dorsal midline incision was made to expose the right sacral nerve. One pair of electrodes (Cardiac pacing wire, A&E Medical, Farmingdale, NJ, United States) were placed around the right sacral nerve (S3) behind the sacral foramen and fixed by a surgical knot (oval cathode 2-3 mm in length in each electrode).…”
Section: Sns Electrodes Implantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrical stimulation of the sacral nerve was also shown to improve mucosal integrity and DAI scores over an 18-month period in a single patient with proctitis (i.e. a condition in which the rectal mucosa is inflamed) ( 119 ), a finding which was confirmed in a rat model of TNBS colitis ( 120–123 ).…”
Section: Bioelectronic Medicine In Ibdmentioning
confidence: 89%